The role of school literacy environtment in strengthening students’ religious competencies - Fithrah Syauqi Abdullah; Praptiningsih; Baehaqi; Yusron Kamal (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to describe the form and characteristics of the school literacy environment at Madrasatul Quran Al Mutawassithoh (MQW) Jajar Islamic Center Sambi, analyze its implementation in Islamic Religious Education (PAI) learning, and identify factors that support and hinder the use of the literacy environment in strengthening students' religious competence. Religious competence is interpreted comprehensively as encompassing religious knowledge, religious attitudes, and students' daily worship practices. This research employs a qualitative approach, incorporating a field study. The research subjects were 7th- to 9th-grade students, while informants included the madrasah principal, literacy mentor teachers, reading corner managers, and students actively involved in literacy activities. Data collection techniques included in-depth interviews, participant observation, and documentation, with data validation through triangulation of techniques and sources. Data analysis was conducted through open, axial, and selective coding, as well as analytical and reflective triangulation. The results indicate that the literacy environment at MQW is built as an ecosystem integrated with Islamic boarding school traditions, through reading corner facilities, a book study program, and the habit of reading the Quran and Islamic literature. This environment supports the development of religious character and an understanding of Islamic values in students. Supporting factors include teacher involvement, a diversity of reading materials, and madrasah policies; while barriers include limited time, low reading interest, and inadequate facilities. This research emphasizes the importance of integrating literacy into Islamic Religious Education (PAI) learning to strengthen students' holistic religious competence.